Bipolar disorder: clinical uncertainty, evidence-based medicine and large-scale randomised trials. - Geddes, J; Goodwin, G (2001)
Background The increasing use of the methods of evidence-based medicine to keep up-to-date with the research literature highlights the absence of high-quality evidence in many areas in psychiatry. Aims To outline current uncertainties in the maintenance treatment of bipolar disorder and to describe some of the decisions involved in designing a large simple trial. Method We describe some of the strategies of evidence-based medicine, and how they can be applied in practice, focusing specifically on the area of bipolar disorder. Results One of the key clinical uncertainties in the treatment of bipolar disorder is the place of maintenance drug treatments and their relative efficacy. A large-scale study, the Bipolar Affective DISORDER: Lithium Anticonvulsant Evaluation (BALANCE) trial, is proposed to compare the effectiveness of lithium, valproate and the combination of lithium and valproate. Conclusions Providing reliable answers to key clinical questions in psychiatry will require new approaches to clinical trials. These will need to be far larger than previously appreciated and will therefore need to be collaborative ventures involving front-line clinicians.